Pengaruh Komunikasi dan Budaya Organisasi terhadap Kinerja Pegawai Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Lestari, Endang Tri; Matondang, Sofiyan (LPPM Universitas Darma Agung, 2020)
Performance is a set of measures regarding how well a job can be done compared with established assessment standards. This study aims at determining the effect of communication and organizational culture partially and simultaneously on the performance of employees of the Medan City Regional Tax and Retribution Management Agency. The population of this study is 329 employees of the Medan City Regional Tax and Retribution Management Agency. Slovin formula was used to determine the number of samples, obtained as many as 181 people. Data collection techniques in this research were questionnaire, interview and documentation study. While the data analysis technique used is the classic assumption test, multiple regression, ttest, Ftest and the coefficient of determination. The results show that there is a significant influence of communication on employee performance. There is a significant influence of work culture on employee performance. There is a significant influence of communication and organizational culture simultaneously on the performance of employees of the Medan City Regional Tax and Retribution Management Agency. The coefficient of determination (R Square) is 0.638, meaning that variations in employee performance can be explained by communication and organizational culture by 63.80%, while the remaining 36.20% is again explained by other factors, such as the work environment, training and other factors which is not explained in this research model.